2010
DOI: 10.1242/dmm.003715
|View full text |Cite
|
Sign up to set email alerts
|

Chemical enhancement of torsinA function in cell and animal models of torsion dystonia

Abstract: SUMMARYMovement disorders represent a significant societal burden for which therapeutic options are limited and focused on treating disease symptomality. Early-onset torsion dystonia (EOTD) is one such disorder characterized by sustained and involuntary muscle contractions that frequently cause repetitive movements or abnormal postures. Transmitted in an autosomal dominant manner with reduced penetrance, EOTD is caused in most cases by the deletion of a glutamic acid (DE) in the DYT1 (also known as TOR1A) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 63 publications
0
51
0
Order By: Relevance
“…Another strategy for identifying novel drugs for dystonia involves screening drugs in animal models of dystonia. A high-throughput screen conducted in a Caenorhabditis elegans model of DYT1 dystonia has revealed potential agents for further study, such as ampicillin [23]. Other promising agents have been identified through pharmacological studies of rodent models of dystonia, including the dystonic dt sz hamster and tottering mouse models [6,24].…”
Section: Potential Sources Of Novel Dystonia Drugsmentioning
confidence: 99%
“…Another strategy for identifying novel drugs for dystonia involves screening drugs in animal models of dystonia. A high-throughput screen conducted in a Caenorhabditis elegans model of DYT1 dystonia has revealed potential agents for further study, such as ampicillin [23]. Other promising agents have been identified through pharmacological studies of rodent models of dystonia, including the dystonic dt sz hamster and tottering mouse models [6,24].…”
Section: Potential Sources Of Novel Dystonia Drugsmentioning
confidence: 99%
“…In this regard, overexpression of C. elegans TOR-2 or human torsinA can reduce protein aggregation resulting from polyglutamine repeats (Fig. 3A-C) or α-synuclein in vivo [65,79,80]. Overexpression of human torsinA in H4 neuroglioma cells expressing α-synuclein also display significantly reduced protein aggregation [81].…”
Section: Application Of C Elegans To Dyt1 Dystonia Researchmentioning
confidence: 95%
“…A survey of a few worm-to-cell culture translational studies reveals wide ranging fold Ethosuximide 2 mg/ml 30 μg/ml 66X [52] differences between these experimental systems, wherein 0.5× to 160× chemical was used in the C. elegans studies (Table 3). It should be noted, however, that in most of these studies, only a single concentration of chemical was examined in either the worm or cell culture experiments [26,45,54]. Thus, it is likely that the minimum fold difference required for a biological response is not accurately represented in these studies, nor was it the goal for the cited literature.…”
Section: Chemical Modifiers Are Readily Analyzed In C Elegans α-Synumentioning
confidence: 99%
“…This advantage of C. elegans research can also facilitate systematic drug discovery efforts in distinct genetic backgrounds. Cao et al [54] reported results of a C. elegans-based small molecule screen to identify compounds that modulate the chaperone-like activity of torsinA. Using multiple transgenic lines and thousands of animals, molecules that selectively altered the activity of WT versus ΔE torsinA with statistically substantial effect could be delineated; this facilitated prioritization for downstream experimentation in mammalian models.…”
Section: Application Of C Elegans To Dystonia Researchmentioning
confidence: 99%
See 1 more Smart Citation